INTRODUCING ENGLISH LANGUAGE USING TOTAL PHYSICAL RESPONSE TO YOUNG LEARNERS - Kurniati, Lely; Sada, Clarry; Susilowati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Â Abstract: The purpose of this research is to answer the question: â€œHow effective is TPR method in teaching English to young learner?â€. The method of this research is pre-experimental research. The sample of this research was students of 1A of SDN 08 Kubu Raya which consisted of 25 students.Â The treatments were given three times in order to know the effectiveness of teaching English using Total Physical response. The technique of data collecting was multiple choices test that consisted of colorful pictures about part of body and color; and there was an oral test where the students should response the teacherâ€™s command physically. The research finding showed that the mean score of pretest was 6.17 and the mean score of posttest was 7.87 and categorized â€œgoodâ€. The result of effect size of treatment was 2.48. It was categorized â€œhighly effectiveâ€ because the result of 2.48 was higher than 0.80 that was the high level of effectiveness on effect size criteria proposed by Burn (ES > 0.8 = 2.01 > 0.8). From the computation, it could be concluded that the teaching English using Total Physical response was â€œhighly effectiveâ€. Â Key Word: TPR, Young learner, Pre Experimental Â Abstrak: Tujuan dari penelitian ini adalah untuk menjawab pertanyaan: â€œ Seberapa efektif metode mengajar menggunakan Total Physical response dalam mengajar anak-anak?â€. Metode penelitian yang digunakan dalam penelitian ini adalah pre-ekperimental. Sampel yang diamati dalam penelitian ini adalah siswa kelas 1A SDN 08 Kubu Raya yang terdiri dari 25 siswa. Untuk mengetahui keefektifan dalam mengajar Bahasa Inggris menggunakan metode Total Physical Response, peneliti memberikan treatment sebanyak tiga kali. Teknik yang digunakan untuk mengumpulkan data adalah tes pilihan ganda yang terdiri dari gambar-gambar berwarna tentang bagian tubuh dan warna. Peneliti juga memberikan test lisan dimana siswa harus mampu merespon petunjuk yang diberikan berupa gerakan. Hasil dari penelitian menunjukkan data bahwa skor rata-rata pretest adalah 6.17 dan data skor rata-rata posttest adalah 7.87 dan hasil ini masuk kategori â€œBaikâ€. Sementara nilai dari pengaruh treatment adalah 2.48, dan dikatetegorikan â€œsangat efektifâ€ karena hasil dari treatment lebih tinggi dari 0.80 yang merupakan level tertinggi dari kriteria keefektifan berdasarkan usulan Burns. Berdasarkan hasil tersebut, dapat disimpulkan bahwa mengajar Bahasa Inggris menggunakan metode Total Physical Response adalah â€œsangat efektifâ€. Â Kata kunci: TPR, anak-anak, Pre-eksperimental